2013
DOI: 10.1371/journal.ppat.1003234
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin Signaling Is Initiated by the Viral Polymerase in HCV-linked Tumorigenesis

Abstract: Exposure to hepatitis C virus (HCV) typically results in chronic infection that leads to progressive liver disease ranging from mild inflammation to severe fibrosis and cirrhosis as well as primary liver cancer. HCV triggers innate immune signaling within the infected hepatocyte, a first step in mounting of the adaptive response against HCV infection. Persistent inflammation is strongly associated with liver tumorigenesis. The goal of our work was to investigate the initiation of the inflammatory processes tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…This is typically the outcome of HCV infections, where chronic inflammation is associated with many adverse effects, notably, liver fibrosis, cirrhosis, and HCC. We along with others have previously reported that NS5B, the HCV RNA-dependent RNA polymerase, induces expression of proinflammatory cytokines (12,13). Double-stranded RNA, generated by viral RNA polymerases during replication and transcription of viral genomes, is a common PAMP recognized by the immune system during infection by RNA viruses.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This is typically the outcome of HCV infections, where chronic inflammation is associated with many adverse effects, notably, liver fibrosis, cirrhosis, and HCC. We along with others have previously reported that NS5B, the HCV RNA-dependent RNA polymerase, induces expression of proinflammatory cytokines (12,13). Double-stranded RNA, generated by viral RNA polymerases during replication and transcription of viral genomes, is a common PAMP recognized by the immune system during infection by RNA viruses.…”
Section: Discussionmentioning
confidence: 84%
“…It has previously been reported that the HCV core and NS3 proteins induce expression of proinflammatory cytokines through as yet to be identified mechanisms (9,10). More recently, we along with others have shown that NS5B, the HCV RNA-dependent RNA polymerase, activates innate immune signaling through the production of small RNA species that are recognized by intracellular receptors and give rise to cytokine production, including type I interferons (11)(12)(13). Thus, expression of viral gene products fuels the persistence of inflammatory signaling.…”
Section: It Is Thus Of Considerable Interest To Investigate What Initmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently, a dramatic upregulation in lymphotoxin-β levels was identified in tumors from HCV transgenic mice, which was accompanied by activation of NF-κB, elevated chemokines, and intra-tumoral recruitment of mononuclear cells (200) (Figure 3B). Inactivation of IKKβ reduced the tumor rate in these animals (200).…”
Section: Oxidative Stress and Pathogenesis Of Hccmentioning
confidence: 98%